W-LEACH Based Dynamic Adaptive Data Aggregation Algorithm for Wireless Sensor Networks. (18th September 2013) - Abdulsalam, Hanady M.; Ali, Bader A.
We consider the problem of data aggregation for nonuniform and evolving wireless sensor networks. We introduce a new data aggregation algorithm that is able to run on uniform, non-uniform, and evolving networks while maintaining the data accuracy. In addition, the algorithm is able to handle sudden bursts in the underlying data by recording the data in the area of interest for the whole event duration. Experimental results on real and synthetic data show that the algorithm performs well in terms of extending the lifetime of the network, maintaining the original distribution of the sensors as long as possible, maintaining the accuracy of the sensed data, and being able to detect and handle sudden bursts of data.